2001
DOI: 10.1074/jbc.m100301200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Insertion of the Heptameric Staphylococcal α-Toxin Pore

Abstract: Staphylococcal ␣-toxin forms heptameric pores on eukaryotic cells. After binding to the cell membrane in its monomeric form, the toxin first assembles into a heptameric pre-pore. Subsequently, the pre-pore transforms into the final pore by membrane insertion of an amphipathic ␤-barrel, which comprises the "central loop" domains of all heptamer subunits. The process of membrane insertion was analyzed here using a set of functionally altered toxin mutants. The results show that insertion may be initiated within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Therefore, the stimulation of the prepore to pore transition by the N terminus of ␣HL must be independent of the final conformation of the N terminus and its sequence. In an earlier study, Valeva and coworkers (52) provided evidence that, during heteroheptamer formation by certain pairs of mutant ␣HL subunits, the N terminus in one class of subunits can activate its own pre-stem intramolecularly and that this activation is transmitted intermolecularly within the prepore to the pre-stem of a normally defective subunit. Further, when the part of the pre-stem that becomes the lower half of the ␤ barrel is deleted, the resulting mutant assembles spontaneously in the absence of membranes to form heptameric structures in which the N termini have formed latches (37), again indicating a cooperative interaction between the N terminus and the pre-stem.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the stimulation of the prepore to pore transition by the N terminus of ␣HL must be independent of the final conformation of the N terminus and its sequence. In an earlier study, Valeva and coworkers (52) provided evidence that, during heteroheptamer formation by certain pairs of mutant ␣HL subunits, the N terminus in one class of subunits can activate its own pre-stem intramolecularly and that this activation is transmitted intermolecularly within the prepore to the pre-stem of a normally defective subunit. Further, when the part of the pre-stem that becomes the lower half of the ␤ barrel is deleted, the resulting mutant assembles spontaneously in the absence of membranes to form heptameric structures in which the N termini have formed latches (37), again indicating a cooperative interaction between the N terminus and the pre-stem.…”
Section: Discussionmentioning
confidence: 99%
“…Amphiphilic structures play a role in the biological interactions of many proteins and peptides that participate in membrane dependent processes. These membrane interactive structures may be classified as possessing either: primary, secondary or tertiary amphiphilicity, with each having a range of effects on lipid organisation [1,[12][13][14][15][16][17][18][19][20].…”
Section: Protein Structural Amphiphilicitymentioning
confidence: 99%
“…This arrangement of amino acid residues allows these structures to form a barrier between aqueous and hydrophobic environments and such structures are now recognised as major protein secondary structural elements, having an important role in a range of membrane dependent processes [1,[12][13][14][15][16][17][18][19][20]. Amphiphilic β-sheet occurs in a number of membrane interactive molecules including: the proteins translocation machinery of mitochondrial and plastid outer membranes [32], bacterial protein toxins [20] such as the heptameric β-barrel pore formed by molecules of staphylococcal α-toxin [13,[33][34][35] and bacterial porins [36]. Amphiphilic α-helices were recognised within the molecules of myoglobin and haemoglobin during the mid sixties [37] and in a major study, were later identified within apolipoproteins by Segrest et al, [38].…”
Section: Protein Structural Amphiphilicitymentioning
confidence: 99%
“…Biochemical analyses of R-HL pore formation have revealed two intermediate states: the membrane-bound monomer and the heptameric pre-pore complex (e.g., refs 39, 40, and 53). Oligomerization precedes membrane insertion during pore formation, and TMH insertion involves interaction among neighboring protomers (28,40,54,55). A comparison of the monomeric structure of LukF and the oligomeric structure of the homologous R-HL revealed that the β-sandwich and rim domains behave as rigid bodies that adopt different relative conformations in the monomer and the heptamer due to small changes spread over a number of residues at the junction between the β-sandwich and rim domains (Figure 1).…”
mentioning
confidence: 99%